Minecraft for dummies, portable edition - Cordeiro, Jacob. (John Wiley & Sons, Inc., 2013)
Get started in minecraft or go deeper - this book helps you both: Playing minecraft, creative experience. if you've been curious and want to get started, this book shows you ropes. And if you know the basics but long to became a mad scientist or venture into hardcore mode, you'll find out how to do that too. Learn to play minecraft and enjoy andless entertainment.